Solomon Islands - Diamond, Judith (Chicago : Childrens Press, 1995)
Discusses the geography, history, religion, economy, people, and everyday life of the diverse peoples of the Solomon Islands in the South Pacific Ocean.
Includes index.
7.0
5-8
Keywords: Solomon Islands -- Juvenile literature; Solomon Islands; Solomon Islands